Investigating the effect of geometric parameters on hydrodynamic and hydro-acoustic performances of submerged propellers. (September 2021) - Razaghian, A.H.; Ebrahimi, A.; Zahedi, F.; Javanmardi, M.R.; Seif, M.S.
Abstract: The hydro-acoustic analysis of submerged propellers is an important issue in marine industries, which is examined to reduce the vibrations and noise level of vessels alongside reducing fuel consumption and improving hydrodynamic efficiency. B-series propellers are common propellers whose hydrodynamic and acoustic investigation through applying suitable rake, and skew angle can offer proper results to designers for enhancing the hydrodynamic performance and reducing noise. In this study, a model of the five-bladed B-series propeller with the normal skew angle is chosen. The effects of geometric parameters, including the rake angle, skew angle, geometric pitch ratio, and the number of blades on the hydrodynamic and acoustic performance of propeller, are numerically investigated under non-cavitating conditions. In the numerical analysis, RANS equations are solved using the finite volume method through k-ε turbulence modeling, and the hydrodynamic characteristics of the propellers are evaluated at different flow conditions. In addition, the noise of propellers is calculated using FW-H formulation in defined receivers. For validation of the numerical results, the model of propeller is tested in the K23 cavitation tunnel at the Sharif University of Technology. Results show that the numerical results are in good agreement with experimental results and other numerical studies. Moreover, the effects of changes of geometric parameters on the hydrodynamic and acoustic performance of the propeller are investigated. According to the results, the far-field can be defined relative to the propeller's radius (R). By increasing the rake angle, geometric pitch ratio, and blade numbers individually, the hydrodynamic efficiency decreases in each advance ratio. The overall SPL downstream of the propeller is higher than the rotation plane, and the five and 7-blade propellers can provide desirable SPL acoustically in this propeller type.